Fungal Endophytes as Growth Promoters and Inducers of Resistance in Tomato (Lycopersicon esculentum Mill.) against Alternaria solani: Life Sciences-Botany for Medicinal science - Amruthesh, Kestur Nagaraj *; Murali, Mahadevamurthy; Sujatha, Hulimavu Shivanna (International Journal of Life Science and Pharma Research, 2021)
Bio control strategies are gaining importance presently due to adverse effects caused by chemical pesticides on the environment. During our study, a total of 78 fungal endophytes were isolated from five medicinally important plants and evaluated for their efficacy in inducing resistance against the early blight pathogen caused by Alternaria solani. Among the isolates evaluated, only five endophytes were able to antagonize A. solani with a maximum inhibition of 58.53% offered by ENSM-08. All the antagonistic endophytes were molecularly identified based on ITS1 and ITS4 regions and sequence analysis was submitted to GenBank, NCBI to acquire accession numbers. In addition, seed treatment with the conidial suspension of the antagonistic fungal endophytes were able to enhance seed, vegetative and reproductive growth parameters in tomatoes with the highest enhancement observed upon the application of Pestalotiopsis microspora- ENSM-08. Also, seed treatments with select endophytes were also able to induce resistance in tomato plants against the early blight pathogen with a maximum protection of 70.25% observed in P. microspora- ENSM-08 treated plants. The results of the study validate the application of fungal endophytes as inoculants for sustainable agriculture.